Probing sectoral networks of ownership in publicly listed financial companies in the Philippines - Aubrey D. Tabuga; Ramonette B. Serafica; Madeleine Louise S. Bai\~no (Philippine Institute for Development Studies (PIDS), 2024)
This paper aims to explore ownership networks of publicly listed financial institutions in the Philippines. It covers the second phase of a research project on financial networks and builds on the analyses done in Tabuga, Ruiz, Serafica and Bai\~no (2024) which aims to provide an understanding of the underlying network structure that may influence financial sector development and stability in the Philippines. The current paper further expounds on the connections examined in the first paper - focusing on the extent of financial institutions' network in other sectors, assessing connection roles in the network. In this report, the network which illustrates ownership and investment relationships has been expanded to include entities with relatively smaller shares emphasizing possible importance of relatively weaker ties. By identifying the sectors and subsectors of nodes in the network, this paper aims to provide a deeper understanding of the extent of network of the country's publicly listed financial institutions. Furthermore, it aims to draw useful knowledge that may be useful for policy formulation and financial supervision/regulation.
Keywords: 330; ownership networks; publicly listed financial institutions; financial networks; network structure; investment relationships; inter-sector connections; network analysis